Vegetation degradation assessment in Bornuur, Tuv province, Mongolia - Davaanyam, Otgontsetseg; Batbaatar, Byambasuren; Nyam-Osor, Tuguldur; Tsetsegmaa, Ganchudur (Mongolian Journal of Botany, 2023)
Desertification was determined as land degradation in arid, semi-arid, and dry sub-humid areas resulting from various factors, including climatic variations and human activities, in other words, it is a reduction in land productivity. Thus, vegetation cover and its dynamic, reflecting land productivity, can be accepted as a representation of land degradation and desertification. Vegetation degradation in arid and semi-arid land has been exposed by community change including changes in species composition and reduction in projective cover, aboveground biomass, and species diversity. However, vegetation degradation varies in natural zones and land use types. In this research, we aimed to determine vegetation degradation in Bornuur soum, Tuv province based on vegetation projected cover, species composition, and diversity. As a result of vegetation surveys at a total of 13 sites throughout the territory and vegetation map, 50.1 percent of the total territory is very strong, 9.1 percent strong, 0.8 percent moderate, and 40 percent in light degradation, separately. Vegetation degradation mainly occurs in plain, small hills, mounds, and lower slopes of high mountains, their valleys, and river valleys or meadows. Community composition was profoundly changed in this area, such as community major species were invaded by digression species including Artemisia frigida, Artemisia adamsii, Carex duriuscula, Potentilla acaulis, Convolvulus ammanii, adapting and predominating at degraded land. The main factors that lead to degradation were agricultural activities, overgrazing and local travel, especially, its effects on the northwest part of the territory like steppe and mountain steppe in Nart, Arangat, Dund Us, and river valleys of Boroo, Shavart, Shivert, Sujigt. Төв аймгийн Борнуур сумын ургамал нөмрөгийн доройтол Хураангуй. Цөлжилт, газрын доройтол гэдэг нь хуурай гандуу, чийг дутмаг бүс нутагт газрын бүтээмж буурах үзэгдэл бөгөөд газрын бүтээмжийг илтгэж чадах нэг үзүүлэлт бол ургамал нөмрөг юм. Тиймээс ургамал нөмрөгт гарч буй өөрчлөлтүүдээр газрын доройтлыг илэрхийлэх боломжтой гэж үздэг. Хуурай, гандуу бүс нутгийн ургамал нөмрөгийн доройтол нь ургамал бүлгэмдлийн зүйлийн бүрэлдэхүүн өөрчлөгдөх, тусгагийн бүрхэц, газрын дээрх биомасс болон ургамлын олон янз байдал буурах зэргээр илэрч байна. Гэвч байгалийн бүс бүслүүр, газар ашиглалтын эрчим зэргээс шалтгаалан ургамал нөмрөгт илэрч буй доройтлын хэлбэрүүд нь харилцан адилгүй юм. Бид энэхүү судалгааны хүрээнд Төв аймгийн Борнуур сумын ургамал нөмрөгийн төлөв байдал, доройтлыг ургамал бүлгэмдлийн зүйлийн бүрэлдэхүүн, тусгагийн бүрхэц, олон янз байдал зэрэгт үндэслэн тогтоохыг зорьсон болно. Сумын хэмжээнд нийт 13 цэгт бичиглэл судалгаа хийж, ургамал нөмрөгийн доройтлын зурагт үндэслэн тооцсон дүнгээр нийт нутаг дэвсгэрийн 50.1% маш хүчтэй, 9.1% хүчтэй, 0.8% дунд, 40% бага зэрэг доройтсон гэж тооцлоо. Ургамал нөмрөгийн доройтол голдуу тал хөндий, толгод, бэсрэг ба нам уулсын бэл хормой, тэдгээрийн хоорондын хөндий, гол горхины ай сав, татамд явагдаж байна. Энд бүлгэмдлийн бүтэц өөрчлөгдөж бүлгэмдлийн үндсэн ургамлуудын оролцоо багасаж, доройтлын таниур ургамлуудаас Агь (Artemisia frigida), Адамсийн шарилж (Artemisia adamsii), Ширэг улалж (Carex duriuscula), Ишгүй гичгэнэ (Potentilla acaulis), Амманы сэдэргэнэ (Convolvulus ammanii) зэрэг ургамлууд зонхилох болсон байна. Ялангуяа нутгийн баруун хойд хэсгийн Нарт, Арангат, Дунд ус зэрэг нам уулсын хээр болон Бороо, Шаварт, Шивэрт, Сүжигт зэрэг голын хөндий газар тариалан болон аялал жуулчлал, малын хөлөөр хүчтэй доройтсон байна. Түлхүүр үгс: доройтлын таниур ургамал, газрын доройтол, ургамлын зүйлийн бүрэлдэхүүн, олон янз байдал, тусгагийн бүрхэц, цөлжилт